EVALUATING HEART HEALTH: AN ANALYSIS OF DALLAS HEART WALK PARTICIPANTS - Thomas, Rebecca; Anderson, Luke; Lewis, Richard (International Research Journal of Sociology, Psychology and Anthropology, 2024)
This study examines the impact of self-reported health behaviors and the health belief theory on participants in hearthealthy events, such as the Dallas Heart Walk, which supports the American Heart Association's mission to reduce cardiovascular disease and stroke. The American Heart Association developed Life's Simple 7® to assess cardiovascular health through seven metrics, including blood glucose, blood pressure, cholesterol, diet, weight, physical activity, and smoking status. Heart disease and stroke are leading causes of death in the United States, and the AHA's goal is to improve cardiovascular health and reduce deaths by 20% by 2020. The study aims to understand how participants' health beliefs and behaviors align with these goals and whether engagement in heart-healthy events influences their cardiovascular health.